THE EFFECTIVENESS OF STUDENTS WORKSHEET BASED ON INQUIRY BY DESIGN ARGUMENTATION ACTIVITY IN BRYOPHYTE - Bil Laila; Rinie Puspitawati (Berkala Ilmiah Pendidikan Biologi (BioEdu), 2019)
Abstract This research was aimed to describe the validity and the effectiveness of student worksheet based on inquiry by design argumentation activity in Bryophyte. The student worksheet was developed by Fenrich cycle (1997). The research stage was begun with  the curriculum, concept, indicator and student analysis. Design and development worksheet were done in Biology Department, Faculty of Mathematics and Natural  Science, Universitas Negeri Surabaya. The student worksheet was implemented by the twelve 10th grade student of SMA Negeri 18 Surabaya. The data of student worksheet validity obtained from the validation by validators. The data of worksheet effectiveness obtained from argumentation test by students. Based on validity result by the validators, showed that the student worksheet was classified as very valid with average score of 3.97. Based on effectiveness result, showed that students was classified as good argumentation with score 75% and 60.19% students can made a claim with data so the student worksheet was able to implemented in the learning activity. Keywords : student worksheet, inquiry, bryophyte, argumentation ability